2002
DOI: 10.1590/s0074-02762002000900022
|View full text |Cite
|
Sign up to set email alerts
|

Antibody isotype responses to egg antigens in human chronic Schistosomiasis mansoni before and after treatment

Abstract: In the present communication we analyzed the levels of IgG1, IgG2, IgG3, IgG4 and IgE Analysis of antibody responses to diferent antigens in patients' sera shows that the slow development of immunity to reinfection after treatment of Schistosoma infection is partially atributable to the continued presence of blocking antibodies in susceptible individuals, particularly IgG4 and IgG2 (Demeure et al. 1993). The role of IgE in several imune mechanisms against the parasite has been described in vitro, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…The finding that dying worms provide the main source of protective antigen fits with several studies showing that praziquantel treatment, which kills adult schistosomes but has little effect on immature worms (23), can boost antibody responses associated with protection against reinfection (20,24). The finding that protective immunity is likely to principally target fecundity is supported by the findings that lower levels of S. haematobium egg output were found relative to levels of circulating anodic antigen (a marker for worm burden) in adults than in children (25), and that S. haematobium fecundity is reduced by the immune response in mice (26).…”
Section: Discussionsupporting
confidence: 80%
“…The finding that dying worms provide the main source of protective antigen fits with several studies showing that praziquantel treatment, which kills adult schistosomes but has little effect on immature worms (23), can boost antibody responses associated with protection against reinfection (20,24). The finding that protective immunity is likely to principally target fecundity is supported by the findings that lower levels of S. haematobium egg output were found relative to levels of circulating anodic antigen (a marker for worm burden) in adults than in children (25), and that S. haematobium fecundity is reduced by the immune response in mice (26).…”
Section: Discussionsupporting
confidence: 80%
“…This correlates with the age-dependent development of human immunological resistance to reinfection with S. mansoni , which is also associated with the presence of anti-tegument IgG antibodies (Karanja et al, 2002). In addition, it has been proposed that the resistance to re-infection following chemotherapy with praziquantel, is mediated by antibodies specific to schistosome antigens released upon worm death that are not normally encountered by the host immune response (Mutapi et al, 1998; Gomes et al, 2002). These observations prompted searches to identify those molecules recognized by antibodies taken from RA cercariae-vaccinated mice, or humans resistant to re-infection.…”
mentioning
confidence: 99%
“…In summary, although the level of antiparasite IgG4 tends to peak in younger age groups, it is also found to be elevated in active Schistosoma infections among adults. 40,48 In our evaluation, although our sampling strategy and small sample size of the triple test group did not allow for a breakdown of the test characteristic analysis by age, it does not seem that IgG4 positivity differed greatly depending on age in those participants positive for S. haematobium infection by egg counting (Table 4). Furthermore, age distribution was fairly uniform across both the ELISA subset and the group as a whole.…”
Section: Discussionmentioning
confidence: 89%
“…24,28,44,45 Whereas studies have shown lower IgG4 levels in lighter infections, the correlation between IgG4 positivity and infection status is high (with greater than 90-95% positivity in infected subjects), making it a useful marker for current infection. 26,39,40,46 Treatment effects on antischistosome IgG4 have been varied across studies and can be difficult to interpret given the possibility of reinfection, differences in methodology, and the ideal time post-treatment to test. 45 Grogan and others 28,47 showed a persistence of IgG4 levels against Schistosoma adult worm antigens in both adults and children 5 weeks and 2 years after treatment, whereas IgG4 levels against egg antigens declined in all groups at these intervals post-treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation